Inter and Intraspecific Genomic Divergence in Drosophila montana Shows Evidence for Cold Adaptation. (13th July 2018) - Parker, Darren J; Wiberg, R Axel W; Trivedi, Urmi; Tyukmaeva, Venera I; Gharbi, Karim; Butlin, Roger K; Hoikkala, Anneli; Kankare, Maaria; Ritchie, Michael G
Abstract: The genomes of species that are ecological specialists will likely contain signatures of genomic adaptation to their niche. However, distinguishing genes related to ecological specialism from other sources of selection and more random changes is a challenge. Here, we describe the genome of Drosophila montana, which is the most extremely cold-adapted Drosophila species known. We use branch tests to identify genes showing accelerated divergence in contrasts between cold- and warm-adapted species and identify about 250 genes that show differences, possibly driven by a lower synonymous substitution rate in cold-adapted species. We also look for evidence of accelerated divergence between D. montana and D. virilis, a previously sequenced relative, but do not find strong evidence for divergent selection on coding sequence variation. Divergent genes are involved in a variety of functions, including cuticular and olfactory processes. Finally, we also resequenced three populations of D. montana from across its ecological and geographic range. Outlier loci were more likely to be found on the X chromosome and there was a greater than expected overlap between population outliers and those genes implicated in cold adaptation between Drosophila species, implying some continuity of selective process at these different evolutionary scales.